If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -5 = 2x + 6 Reorder the terms: -5 + -3x = 2x + 6 Reorder the terms: -5 + -3x = 6 + 2x Solving -5 + -3x = 6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -5 + -3x + -2x = 6 + 2x + -2x Combine like terms: -3x + -2x = -5x -5 + -5x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 -5 + -5x = 6 + 0 -5 + -5x = 6 Add '5' to each side of the equation. -5 + 5 + -5x = 6 + 5 Combine like terms: -5 + 5 = 0 0 + -5x = 6 + 5 -5x = 6 + 5 Combine like terms: 6 + 5 = 11 -5x = 11 Divide each side by '-5'. x = -2.2 Simplifying x = -2.2
| 8(a+5)=64 | | 4a+7b+7+3a= | | 12+5y=93 | | -6(x-5)+3x=3x-6 | | 180n-360/n=135 | | 4y=8y+8 | | 8x+7=10x-11 | | 180n-360/n=350 | | 68=9c-4 | | 12=6-5x+3 | | 180n-360/n=35 | | 17/6x/2 | | x/10=3/2 | | 18m^2-15m=42 | | 5e-8=42 | | 3x+20-5x=32 | | w-7/8=6 | | x^2-3x-100=9 | | 5(3x-3)=120 | | -360/n | | P(p-4)=18 | | 5a+35g= | | tan(3x)=y | | 12b-3=3b+6 | | 12x-192=4x | | 12n+10=2(n+1) | | 6y^2+96=18 | | 5/4-1/2 | | y=x^2-3/2x | | x*x+1=9 | | 11=u-9 | | 7/a=3/5 |